TINGKAT PENERAPAN SISTEM PERTANIAN TERINTEGRASI SAPI BALI DAN TANAMAN PALAWIJA DI DESA SELUMBUNG DAN DESA MANGGIS, KECAMATAN MANGGIS, KABUPATEN KARANGASEM - Desimiyanti, N. K. Mita; Nuraini, K.; Suarta, I G. (Jurnal Peternakan Tropika, 2014)
The research aims to find out the level of simantri implementation based Bali cattle and crops and the factors that influence was conducted in Selumbung and Manggis villages, Manggis district, Karangasem regency from January to May 2013. Research site were selection using the purposive sampling method , even though respondents determination by the census method. Study used 37 farmers as respondents who are all simantri group members of Selumbung and Manggis villages. Study were used primary and secondary data and measurement of variables using 5 level scale (Singaribum and Efefendi, 1989). Therefore, to determine the relationship of the factors research methods the researcher used courses Spearmen Correlation Coefficient (Siegel, 1977) and to find out the difference of the implementation level, knowledge and attitudes using the Mann Whitney test (U Test). These results were indicated that the level of application-based Simantri Bali cattle and crops in Selumbung Village better  than in Manggis Village, knowledge and attitude variables  have the marked differences between respondents in Selumbung Village and Manggis village. Knowledge factors, attitude and ages have relationship to application-based simantri in Selumbung village. In Manggis village only knowledge factors that have a relationship with the applications.
Keywords: Knowledge, Applications, Respondence, Integrated Farming System